Daily Sedation Interruption Versus Continuous Sedation for Reducing Mechanical Ventilation Duration in the Intensive Care Unit: A Meta-Analysis - Indah Ika Suryaningsih H; Ayu Yesi Agustina (Journal of Anesthesiology and Clinical Research, 2026)
Introduction: Mechanical ventilation is a critical intervention in intensive care units, yet prolonged ventilation increases complications including ventilator-associated pneumonia, delirium, and mortality. Daily sedation interruption (DSI) has been proposed as a strategy to reduce ventilation duration, but evidence remains inconsistent. Methods: A systematic review and meta-analysis was conducted searching PubMed, Embase, Cochrane Library, and Web of Science from inception to March 2024. Randomised controlled trials (RCTs) and observational studies comparing DSI with continuous sedation were included. The primary outcome was duration of mechanical ventilation. Pooled standardised mean difference (SMD) and 95% confidence intervals (CI) were calculated using Hedges’ g with a random-effects model. Heterogeneity was assessed using I² statistics, and subgroup analyses stratified by intensive care unit type and study design. Results: Ten studies comprising 2,011 participants were included. Pooled SMD for ventilation duration was −0.3655 (95% CI −0.7611 to 0.0301; p = 0.0662), indicating a non-significant trend favouring DSI, with very high heterogeneity (I² = 91.54%). Subgroup analysis in general intensive care units (three studies, n = 426) demonstrated significant reduction in ventilation duration (SMD = −0.6763, 95% CI −0.1265 to −0.2262; p = 0.0231; I² = 20.38%), whereas medical (three studies) and medical-surgical (three studies) units showed non-significant effects. Sensitivity analysis indicated robustness of findings when studies by Nassar Jr and Mehta (2016) were sequentially excluded. Conclusion: Daily sedation interruption showed a non-significant trend towards reducing mechanical ventilation duration in pooled analysis, with significant benefit demonstrated specifically in general intensive care units. High heterogeneity suggests practice variation in DSI protocols and patient populations influences outcomes. Future standardised DSI protocols and trials in homogeneous populations are warranted.